(untitled) (Research, Society and Development, 2021)
Research with forage palm in semi-arid regions are driven by the importance of its production of juicy fruits and stems (cladodes), which guarantee a source of water and nutrients in quantity and quality for people and animals in these places. Recently, the search for natural substances, including secondary plant metabolites (MSPs), showed an expressive amount of these substances in the forage palm, with effects on food and health. This review was based on the results of scientific research conducted by specialists in the field with the aim of investigating the presence of MSPs and their benefits on the health and nutrition of people and ruminant animals. A positive effect of MSPs was observed, as antioxidants, acting in the prevention of diseases, minimizing chronic diseases in humans and improving animal production, by providing increased nutrient intake, improved rumen fermentation, decreased oxidative stress and methane excretion. Therefore, the usual use of forage palm in the feeding of ruminants in the Brazilian Semiarid region and its richness in MSPs require research to ensure their action when present in the diet of ruminants. Thus, the forage palm deserves attention for its multiple benefits in relation to health and food, in addition to adding value to products of animal and vegetable origin, contributing to the sustainability of arid regions.